Learning Theories In Family Learning Environments - Haryanto; Henni Ambarsari; Lidwina Elly Marcyanne Kumala; Rilla Sovitriana (Educate : Journal of Education and Learning, 2025)
Research aims to empower parents to create a strong learning environment right in their own homes. By understanding how we learn, educators and parents can develop effective teaching strategies and boost the overall quality of education. In a nutshell, learning theories are crucial for understanding how children process information and how parents can make learning more effective. Parents can utilize various strategies and techniques, drawing from both general learning theories and specific family learning theories, to improve the quality of their children's learning and academic outcomes within the family setting. This study used a qualitative approach, focusing on school-aged children. It delved into real-life events and phenomena using a descriptive qualitative method, primarily through a literature review of theories in learning and family education. The findings show that learning is a relatively permanent change in behavior or potential behavior, stemming from reinforced experience or practice. Essentially, if someone has truly learned something, they'll be able to demonstrate a change in their behavior